Oral Shedding of an Oncogenic Virus Alters the Oral Microbiome in HIV+ Patients - Dai, Lu; Lu, Yong-Chen; Chen, Jungang; Plaisance-Bonstaff, Karlie; Mu, Shengyu; Forrest, J. Craig; Whitby, Denise; Post, Steven R.; Qin, Zhiqiang (Frontiers in Microbiology, 2022)
Kaposi’s Sarcoma (KS) caused by Kaposi’s sarcoma-associated herpesvirus (KSHV) continues to be the most common AIDS-associated tumor. Involvement of the oral cavity represents one of the most common clinical manifestations of this tumor. Numerous types of cancer are associated with the alterations of in components of the microbiome However, little is known about how KSHV coinfection affects the oral microbiome in HIV+ patients, especially in a “pre-cancer” niche. Using 16S rRNA pyrosequencing, we found that oral shedding of KSHV correlated with altered oral microbiome signatures in HIV+ patients, including a reduction in the microbiota diversity, changing the relative composition of specific phyla and species, and regulating microbial functions. Furthermore, we found that Streptococcus sp., one of the most increased species in the oral cavity of HIV+/KSHV+ patients, induced KSHV lytic reactivation in primary oral cells. Together, these data indicate that oral shedding of KSHV may manipulate the oral microbiome to promote viral pathogenesis and tumorigenesis especially in immunocompromised patients.